PENYULUHAN KESEHATAN TENTANG PENTINGNYA MENGGUNAKAN HELM SAAT BERKENDARA DENGAN SEPEDA MOTOR - S. Maliawan; N. Golden; T.G.B. Mahadewa; I.W. Niryana; D.P.W. Wardhana; S. Awyono; K.K. Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
In the year of 2020, 100.028 cases of traffic accident were noted in Indonesia, according to data from the Traffic Corps of the Republic of Indonesia Police (Korlantas Polri). To reduce poor long-term outcome of head injury, a need of appropriate prevention is needed. One easy and effective way to do this is to drive safely according to the traffic guidelines to hinder accident and to wear a helmet. Usage of helmet could effectively protect agains severe and lethal head injury. The basis of university education is the tri dharma which includes education, research, and community service. Bedah Saraf Bersama Masyarakat held by Neurosurgery Residency Programme in FK UNUD / RSUP Sanglah created a health promotion as a form of community service. Health promotion on the importance of using helmet while riding a motorcycle was conducted at PRO 2 RRI FM. Our goal is to educate about the potential for head injuries while driving a motor vehicle and educate the public about the importance of using a helmet when riding a motorcycle. Keywords : Head injury, helmet, health promotion, motorcyc